An intradermal skin test for determination of immunity to varicella. Issue 6 (1st December 2001) - Somekh, E; Bujanover, Y; Tal, G; Dalal, I; Tanay, A; Lehman, D
Abstract : AIMS: To evaluate the usefulness of a diluted, inactivated solution of attenuated varicella vaccine in predicting susceptibility to varicella and its correlation with specific antibody titre to varicella. METHODS: In a prospective blinded study, 63 healthy subjects (aged 2–43 years) were studied. Skin test solution was prepared from vials of OKA strain virus which was inactivated by exposure of the vials to room temperature for 10 days; solution was diluted at 1/50 with normal saline and kept at 4°C until used for skin testing. The material was injected intradermally. Serum samples were drawn prior to skin testing and kept at −70°C until analysis for antibody assay by the indirect fluorescent antibody (IFA) method. RESULTS: Forty three patients were IFA antibody positive; 41 of them reacted to the skin test. One of the 20 IFA negative patients reacted to the skin test. Sixteen patients had two serological tests performed, one month apart. Four out of these 16 patients tested negative with the skin test. All four had negative serology on both samples. Six of the 12 IFA positive patients showed a boost in the antibody titre one month after application of the skin test. The specificity and sensitivity of the skin test compared to the IFA assay were both 95%, and the positive and negative predictive values were 97% and 90% respectively. CONCLUSIONS: Results suggest that a varicella skin test prepared using this simple and relatively cheap method is a safe, sensitive, and specific tool by which to assess immunity to varicella.